Machine Learning to Improve Security Operations Centers - Sousa, Norberto João Gomes Lopes de (2022)
Since the onset of the internet, the world has embraced this new technology and used it to collectively advance Humanity. Companies have followed the trend from the physical to the digital world, taking with them all their associated value. In order to safeguard this value, security needed to evolve, with enterprises employing departments of highly trained professionals. Nevertheless, the ever increasing amount of information in need of evaluation by these professionals requires the deployment of automation techniques, aiding in data analysis and bulk task processing, to reduce detection time and as such improve mitigation. This work proposes a novel tool designed to help in attack detection and alert aggregation, by leveraging machine learning techniques. The proposed solution is described in full and showcased using real data from an example implementation.